Introduction into France of the Japanese oyster (Crassostrea gigas) - Grizel, Henri; Héral, Maurice (ICES Journal of Marine Science, 1991)
The Japanese oyster ( Crassostrea gigas ) has been introduced in France on a large scale to replace cultivation of the Portuguese oyster ( Crassostrea angulata ), affected by a viral disease. The importation took place from 1971 to 1975, with broodstock coming from British Columbia (Canada) and spat from Japan. Good growth rate and success of the natural setting on the French Atlantic coast attested to the success of this implantation, with a production which reached 80 0001 by 1976. The precautionary measures associated with this transfer limited the implantation of an introduced fauna, 15 years after, to: Balanus amphitrite, Aiptasia pulchella and, on the Mediterranean coast, Undaria pinnatifida and Laminaria japonica . The authors also discuss the possible role of Crassostrea gigas in spreading the viral disease. L'huître japonaise ( Crassostrea gigas ) a été introduite massivement en France dans le but de subvenir au remplacement de l'élevage de l'huître portugaise ( Crassostrea angulata ) décimée par une maladie virale. Ces importations effectuées de 1971 è 1975 concernent des géniteurs provenant de Colombie Britannique (Canada) et du naissain en provenance du Japon. De bonnes performances de croissance et le succès du captage sur la côte atlantique française traduisent la réussite de l'implantation de cette espèce dont la production a atteint, dès 1976, 80 000 tonnes. Les précautions associèes á cette importation ont permis de limiter l'implantation dune faune associée dont les principales espéces, 15 ans après, sont: Balanus amphitrite, Aiptasia pulchella et, sur la côte méditerranéenne, Undaria pinnatifida et Laminaria japonica . Enfin est discuté le rôle possible de Crassostrea gigas dans la propagation de la maladie à virus.